Microscopy of the Heart (Springer International Publishing, 2018)
This book provides in depths information on different microscopy approaches and supplies the reader with methods how to untangle highly complex processes involved in physiological and pathophysiological cardiac signaling. Microscopy approaches have established themselves as the quasi gold standard that enables us to appreciate the underlying mechanisms of physiological and pathophysiological cardiac signaling. This book presents the most important microscopy techniques from the level of individual molecule e.g. Förster-Resonance Energy Transfer (FRET), up to cellular and tissue imaging, e.g. electron microscopy (TEM) or light sheet microscopy. The book is intended for graduate students and postdocs in cardiovascular research, imaging and cell biology, pre-clinical and clinical researchers in cardiovascular sciences as well as decision makers of the pharmaceutical industry.